2017
DOI: 10.1590/abd1806-4841.20176638
|View full text |Cite
|
Sign up to set email alerts
|

Frontal fibrosing alopecia and extrafacial lichen planus pigmentosum in a caucasian woman

Abstract: We present the case of a 72-year-old Caucasian woman with frontal fibrosing alopecia of one year’s duration. Eighteen months later, she presented with sudden hyperpigmentation on the submental area, neck and upper chest. Histopathological examination was consistent with lichen planus pigmentosus. This is the report of a unique case of a FFA and extrafacial lichen planus pigmentosus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…However, the majority of patients developed LPP prior to FFA. [38][39][40][41] The most common clinical presentation of facial LPP is diffuse type, followed by reticulated and multiple pigmented macules. 37 In our study, facial hyperpigmentation and facial lentiginous macules were observed in more than half of our patients, most of them had characteristics of LPP as confirmed by trichoscopy of speckled blue-gray dots in dotted patterns, dots in circles or pseudonetwork patterns and loss of facial vellus hairs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the majority of patients developed LPP prior to FFA. [38][39][40][41] The most common clinical presentation of facial LPP is diffuse type, followed by reticulated and multiple pigmented macules. 37 In our study, facial hyperpigmentation and facial lentiginous macules were observed in more than half of our patients, most of them had characteristics of LPP as confirmed by trichoscopy of speckled blue-gray dots in dotted patterns, dots in circles or pseudonetwork patterns and loss of facial vellus hairs.…”
Section: Discussionmentioning
confidence: 99%
“…The onset of LPP can occur before, concurrent with or after scalp hair loss. However, the majority of patients developed LPP prior to FFA 38–41 . The most common clinical presentation of facial LPP is diffuse type, followed by reticulated and multiple pigmented macules 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Their association was first reported by Dlova [31] in 24 Afro-Americans (23 females, 1 male). Later, about 100 cases have been reported worldwide [30,[32][33][34][35][36][37][38][39][40][41][42][43]. Epidemiologic data of the association are conflicting, due to the lack of large case series.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in some studies, FFA precedes the onset of LPPigm, in others LPPigm proceeds to FFA [31, 37, 39, 42]. Interestingly, the association between FFA and LPPigm is rare in Caucasian women with 9 skin phototype ≤III reported cases [32, 35, 39, 40].…”
Section: Discussionmentioning
confidence: 99%
“…Most patients with coexistence of FFA and LPPigm, found in the literature, were cases with facial involvement preceding FFA [31]. In the opinion of some authors, LPPigm and follicular red dots may not just be limited to facial skin [32][33][34]. An increased incidence of LPP (5.7-16.5%), cutaneous or oral mucosal lichen planus (5.2%) as well as lichen planus-type nail involvement or co-existence of FFA and Graham-Little-Piccardi Syndrome has also been reported [35,36].…”
Section: Clinical Manifestations Of Classical Ffamentioning
confidence: 99%